Using workplace safety and health data for injury prevention. - Wiatrowski, William J. (Monthly Labor Review, 2013)
The article discusses how to effectively use workplace health and safety data to determine the root causes of workplace injuries and develop strategies to prevent them. Also cited are the need to focus on five factors like frequency of incidents, sequence of events, and severity of injuries, and the U.S. Bureau of Labor Statistics (BLS) Occupational Safety and Health Statistics program like the Census of Fatal Occupational Injuries (CFOI).